Integrating Water Storage Tank Filtration And Wash Education To Improve Clean Water Quality In Wagir, Malang - Monasari, Ratna; Weddakarti, Eva; Astusi, Fina Andika Frida; Farida, Nike Nur; Nurhadi, Nurhadi; Ekasari, Silvia Rahmi; Aji, Supa Kusuma (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
The community service program at Perum Grand Kencana, Wagir, Malang Regency, was motivated by household reports of fluctuating water clarity and odor in reservoirs and weak routine maintenance practices. To address these issues, the program aimed to improve the suitability of domestic air use by integrating affordable pump and filtration installations with community capacity building. The methodology began with a rapid assessment intervention (field observations, short interviews, and group discussions) to map technical and maintenance conditions, followed by the design and installation of a filtration pump system, operation and maintenance training, and assistance in developing standard operating procedures (SOPs), cleaning schedules, and the division of managerial roles at the neighborhood level. Evaluation was conducted qualitatively through repeated observations, feedback from training participants, and regular reviews of community-managed logbooks to assess SOP implementation and maintenance discipline. The intervention resulted in an easy-to-operate technology package, a concise educational tool, a community-based management structure, and more organized maintenance, which, according to community feedback, was followed by improved perceptions of water clarity and reduced odor. Overall, the combination of technology and community ownership has proven relevant for strengthening reservoir maintenance governance and improving perceptions of quality, and is worthy of replication in similar residential neighborhoods.